Comparative Study of Critical View of Safety vs Infundibular Technique in Laparoscopic Cholecystectomy - Iftikhar, Muhammad; Ahmad, Siddique; Aziz, Khalid (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES: The purpose of this study is to compare the critical view of safety technique with the infundibular technique in laparoscopic cholecystectomy in terms of mean operative time and bile duct injuries (BDI). METHODOLOGY: Between 2018 and 2020, 220 patients had laparoscopic cholecystectomy in the Surgical "A" unit at Hayatabad Medical Complex in Peshawar, Pakistan. The patients were divided into two groups, with the first receiving a critical view of safety and the second receiving an infundibular procedure. Operation time and bile duct injury were compared between the two groups. RESULTS: The operative time was significantly reduced with the critical view of safety (CVS) approach, with a mean time of 35.07 minutes for CVS and 40.58 minutes for infundibular technique, with a significant P-value (0.013). About 17 (7.7%) cases required open cholecystectomy; the conversion rate was higher in the infundibular group, with a significant P-value (<0.001). CONCLUSION: Although the "critical view of safety" requires more patience during dissections than the infundibular approach, it is proven to be faster and is considered a safe procedure in laparoscopic cholecystectomy. KEYWORDS: Critical View of Safety (CVS), Infundibular Technique (IT), Bile Duct Injury (BDI)